Conceptualizing Learner-Focused Pedagogy: Approaches to Instruction and Learning Outcomes - James P. Takona (Journal of Research in Education and Pedagogy, 2025)
This research utilizes a structured narrative literature review methodology to examine the impact of learner-focused pedagogy on student engagement, autonomy, and academic achievement in different educational settings. Databases that included ERIC, JSTOR, Google Scholar, and various others were utilized to collect pertinent research, mainly published from 2013 to 2024. While the emphasis was on recent developments, 13 fundamental studies published prior to 2013 were intentionally included to provide key theoretical foundations, guaranteeing that the review presents both a historical perspective and a progressive synthesis. A structured narrative review was utilized to comprehensively synthesize various perspectives and emerging trends without using PRISMA or Cochrane protocols. The research emphasizes important methods like cooperative learning, ongoing assessments, and the use of technology that encourage critical thinking, self-management, and social growth. The results show that student-centered methods boost participation and develop key 21st-century abilities like problem-solving, adaptability, and teamwork. Nonetheless, obstacles like teacher readiness, institutional inflexibility, and unequal access to resources impede wider adoption. Addressing these obstacles necessitates focused professional growth, flexible curricula, and fair access to technological tools. This research provides actionable suggestions for teachers, decision-makers, and school administrators to create inclusive and flexible educational settings. Upcoming studies should feature systematic reviews following recognized protocols, longitudinal research to gauge lasting effects, and comparative evaluations to examine cross-cultural adaptability. By tackling current obstacles and encouraging evidence-informed methods, learner-centered education can enhance educational results and foster lifelong learning.